NILAI BIOLOGIS MI KERING JAGUNG YANG DISUBSTITUSI TEPUNG JAGUNG TERMODIFIKASI MELALUI HEAT MOISTURE TREATMENT - Nurheni Sri Palupi; Feri Kusnandar; Oke Anandika Lestari (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2015)
The objective of this research was to determine the effects of physical modification of corn flour by heat moisture treatment (110°C, 6 hours) on the biological values of Heat Moisture Treated (HMT)-corn flour obtained as well as corn noodles substituted with the HMT-corn flour. The parameters tested which were directly associated were starch and protein digestibility in vitro while indirect parameters included the resistant starch and insoluble fiber contents. The chemical composition (protein, fat, carbohydrates, starch, amylose and amylopectin) of the substituted corn noodles were analyzed by chemical methods. In vitro dietary fiber of the noodles were determined gravimetrically whereas the resistant starch, starch and protein digestibility for both the HMT-corn flour and corn noodles substituted with 10% HMT-corn flour were determined using spectrophotometry. The HMT-corn flour had higher resistant starch and soluble fiber contents, but lower starch and protein digestibilities. Meanwhile, the substituted corn noodle had higher resistant starch and soluble fiber yet had significantly lower starch digestibility than those of corn noodle without HMT-corn flour.